DREPTUL DE PROPRIETATE ÎN ECONOMIA DE PIAŢĂ (PANGEEA, 2025)
The fact that the definition of ownership mention an exclusive to dispose of goods, denotes two meanings: one is to enjoy these goods, and the second is one that is restricted within the law. This ownership has evolved from primitive peoples to the modern era, especially with deep anchorages in a market economy. In order to be expressed, this right is guaranteed also by the European Court of Human Rights as a culmination of all the rights freely expressed.